Low iron status and cognitive impairment in northern China community-dwelling older adults: a cross-sectional study - Xin, Jimei; Liu, Wei; Li, Wensi; Feng, Qiyue; Hao, Gaiping; Wang, Lei (Frontiers in Nutrition, 2025)
BackgroundThe association between serum iron concentration and cognitive ageing remains inconsistent, particularly in rural Chinese populations where both iron deficiency and excess may coexist.MethodsIn this cross-sectional analysis of 737 community-dwelling adults aged ≥60 years from rural Taiyuan, China, cognitive impairment was assessed with the Chinese-language Mini-Mental State Examination (MMSE) using education-specific cut-offs. Serum iron was quantified by inductively coupled plasma-mass spectrometry and categorized into tertiles (low, medium, high). Multivariable logistic regression models adjusted for sociodemographic, lifestyle and clinical covariates examined independent and joint associations; restricted cubic splines (RCS) evaluated dose–response patterns.ResultsAfter comprehensive adjustment, serum iron demonstrated a non-linear relationship with cognitive impairment risk. Relative to the lowest tertile, medium (OR = 0.61, 95% CI: 0.39–0.95) and high (OR = 0.59, 95% CI: 0.37–0.93) serum iron concentrations were associated with reduced odds of cognitive impairment. Spline analysis suggested a U-shaped relationship: risk decreased with rising serum iron up to a nadir and then trended upward; however, the departure from linearity was not statistically significant (P-nonlinear = 0.194).ConclusionBoth low and high serum iron levels are linked to poorer cognitive performance in this rural cohort, supporting the need to maintain iron within an optimal range for healthy cognitive ageing.